Transformasi budaya Aceh: tari Ratoeh Jaroe menjadi aksesori hijab dengan metode ATUMICS - Aldya Humaira; Anastasia Ary Noviyanti; Fadilah Husna Arief (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
Modernization and globalization have brought significant changes in people's lives, including in local cultures such as Acehnese culture. These changes not only provide challenges, but also threats to the preservation of traditional values and cultural identity. Acehnese society, which is very close to Islamic values, is now starting to experience a cultural shift. For this reason, efforts are needed to preserve culture through media that are relevant to today's lifestyle, namely jewelry. This study aims to revive Acehnese cultural values through a design approach to hijab accessories, which are part of the customs of Acehnese women. Cultural values are analyzed through a typical Acehnese dance, namely the Ratoeh Jaroe dance. The method used is ATUMICS to produce modern hijab accessory designs that still maintain traditional aspects. The output of this study is hijab accessories in the form of ethnic-modern brooch and tuspin that can be a medium for cultural communication as well as an effective means of preserving Acehnese culture.Published Date: 2026-07-26